2011
DOI: 10.1111/j.1365-2834.2011.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse adoption of continuous patient monitoring on acute post-surgical units: managing technology implementation

Abstract: It is strongly recommended that nurse managers identify stakeholders and develop comprehensive plans for monitoring the effects of HIT in their units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Unlike therapeutic devices that directly affect patients, information technology's effect in is changing the way the patient's condition is understood and the way in which care is delivered. [28] Usability, which concerns the way patients utilize the telehealthcare service, is an important indicator for determining future service adjustments and can also yield opportunities to gain further insight into patient status. [29] The results show no significant differences for patients from the two areas in gender, age, and BMI; this is indicative of similar populations for the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike therapeutic devices that directly affect patients, information technology's effect in is changing the way the patient's condition is understood and the way in which care is delivered. [28] Usability, which concerns the way patients utilize the telehealthcare service, is an important indicator for determining future service adjustments and can also yield opportunities to gain further insight into patient status. [29] The results show no significant differences for patients from the two areas in gender, age, and BMI; this is indicative of similar populations for the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Such cooperation can help in bringing together the latest IT expertise and practical clinical expertise in the organization, which is crucial in solving problems that arise during the implementation [29]. This relationship-building can also help in understanding the long-term potential of the technology and therefore give knowledge of new IT that can further contribute to the IT strategy of the healthcare organization [22].…”
Section: Collaboration With the Vendorsmentioning
confidence: 99%
“…Such as scope, schedule, budget of project, change management and implementation plan /strategy [7], [8], [9], [12], [16], [22], [27], [29], [17] 9 25.00%…”
Section: Project Management and Planningmentioning
confidence: 99%
“…In addition, a particular HIS may fit one context but not others; the same HIS was successfully adopted in urgent care but was abandoned when it was introduced to routine patient care due to its poor fit (Ackerman et al, 2012). In another study (Jeskey et al, 2011), HIS designed for critical care was found to be unsuitable for acute care settings. Gough et al (2014) interviewed 125 nurses at five acute care hospitals across two Australian states.…”
Section: Usefulness / Effectivenessmentioning
confidence: 99%
“…Fidelity HIS functionality did not meet the nurses' needs nor support their workflows and practice (Novak et al, 2013;Stevenson et al, 2010); workflow interruptions, additional work (Eley et al, 2009;Lee et al, 2008), unintended consequences (Dowding et al, 2009;Koppel et al, 2005). A particular HIS may fit one context but not others (Ackerman et al, 2012;Gough et al, 2014;Jeskey et al, 2011) Firstly, in regard to usability, Stevenson et al (2010) reviewed five empirical studies published from 2000 to 2009 and reported on nurses' experiences with HIS systems. These studies took place in acute care hospital contexts in USA, Australia, and the UK.…”
Section: Usefulness / Effectivenessmentioning
confidence: 99%